The Effect Of Price And Location On Consumer Buying Interest In Griya Agung Permai Lestari Housing Residence Lahat Regency - M Nur Syukron; Nidyawati Nidyawati; Heri Fitriadi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The purpose of this study was to determine the effect of price and location on consumer purchasing interest in the Griya Agung Permai Lestari housing complex in Lahat Regency. The results showed that (1) price has a significant partial effect on purchasing interest, as evidenced by the calculated t-value > t-table (8.020 > 1.992). (2) location has a significant partial effect on purchasing interest, as evidenced by the calculated t-value > t-table (3.328 > 1.992). (3) price and location have a significant simultaneous effect on consumer purchasing interest in the Griya Agung Permai Lestari housing complex in Lahat Regency, as evidenced by the calculated f-value > f-table (70.833 > 3.968), with a significance value lower than the significance level (a) of 0.05 (0.000 < 0.05).